Super foods for babies and children - Karmel, Annabel (New York : Simon & Schuster, 2001)
Every parent wants the best for their child, to give them the perfect start in life, and that includes their diet and the food they eat. Annabel Karmel understands this better than most - as a trained cook and the mother of three growing children she not only knows what kids should eat but also knows what they will eat. In SuperFoods for Babies and Toddlers, Annabel takes you through your child's first 5 years from weaning babies and feeding whilst teething through fussy toddlers to lunchboxes for school children. As well as discussing the issues of organic versus genetically modified foods, fresh versus convenience, Annabel explains the inherent qualities of certain foods and how they will benefit your child, whether they be foods to promote growth, enhance concentration or boost energy. With extra information on food allergies and intolerances, tips on feeding a vegetarian child and several of Annabel's celebrated meal planners, SuperFoods for Babies and Toddlers is an indispensable guide to nutrition for young children.
Keywords: Cookbook -- Nutrition -- Parenting